Studying the Effect of Magnesium Oxide Nanoparticles Prepared on the Surface of Poly Methyl Methacrylate (Baghdad Science Journal, 2020)
In this paper, magnesium oxide nanoparticles (MgO NPS) have been prepared and characterized and its concentration effect has been studied on polymers surface (MgO NPS). The results showed that the degradation of poly methyl methacrylate increased when using such metal oxide. The results also showed that the metal oxide increased the degradation of poly methyl methacrylate. X-ray diffraction, scanning electron microscopy, atomic force microscopy were used to study the morphological characteristics and size of nano MgO particles analysis. Films were prepared by mixing the different masses of MgO NPS (0.025, 0.05, 0.1, 0.2 and 0.4) % with a polymer solution ratio (W/V) 7 %. Photo- degradation rate was monitored irradiation’s time by measuring the incident frequency of the index value of the hydroxyl coefficient of growth (IOH) at fixed film thickness and constant concentration. Spectrophotometry (IR, and UV. Visible) techniques were used to determine the change in the intensity of the spectrum bundles.